Analytical derivation of charge relaxation time distribution in transistor from current noise spectrum using inverse integral transformation method. (21st February 2018) - Yatabe, Zenji; Inoue, Shinya; Asubar, Joel T.; Kasai, Seiya
Abstract: An analytical technique is proposed to reveal the relaxation time distribution of dynamic charge events using the current noise spectrum of a transistor, by applying an inverse integral transformation to the McWhorter model. In the proposed method, the continuous relaxation-time distribution function G (τ) can be analytically derived from the noise spectra S (ω) without a spectrum deconvolution. The feasibility of the proposed method is demonstrated by characterizing the charge dynamics of tetraphenylporphyrin molecules dispersed on the surface of a GaAs-based nanowire field-effect transistor. Our analysis successfully verified the time constant of the molecule-related dynamic charge events and effects of photo-excitation.